Fundamental planetary science : physics, chemistry, and habitability - Lissauer, Jack Jonathan; De Pater, Imke, 1952- (Cambridge : Cambridge University Press, 2013)
A quantitative introduction to the Solar System and planetary systems science for advanced undergraduate students, this engaging new textbook explains the wide variety of physical, chemical and geological processes that govern the motions and properties of planets. The authors provide an overview of our current knowledge and discuss some of the unanswered questions at the forefront of research in planetary science and astrobiology today. They combine knowledge of the Solar System and the properties of extrasolar planets with astrophysical observations of ongoing star and planet formation, offering a comprehensive model for understanding the origin of planetary systems. The book concludes with an introduction to the fundamental properties of living organisms and the relationship that life has to its host planet. With more than 200 exercises to help students learn how to apply the concepts covered, this textbook is ideal for a one-semester or two-quarter course for undergraduate students.
Machine generated contents note: 1. Introduction; 2. Dynamics; 3. Solar heating and energy transport; 4. Planetary atmospheres; 5. Planetary surfaces; 6. Planetary interiors; 7. Magnetic fields and plasmas; 8. Meteorites; 9. Minor planets; 10. Comets; 11. Planetary rings; 12. Extrasolar planets; 13. Planet formation; 14. Planets and life; Index.
Title from publisher's bibliographic system (viewed on 30 May 2018).
Keywords: elektronické knihy; electronic books; Planetary theory; Planets -- Geology; Planets -- Atmospheres; Planetary rings